PENGARUH DESENTRALISASI FISKAL DAN PERTUMBUHAN EKONOMI TERHADAP KETIMPANGAN ANTAR DAERAH - LATIFAH LATIFAH; DEWI RAHAYU (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to determine the effect of fiscal decentralization and economic growth of South Kalimantan Province on inter-regional inequality. The data used in this study is secondary data with a period of 12 years (time series), which is published once a year by the Central Statistics Agency of the Province of South Kalimantan. The data needed is in the form of data on total balancing funds, economic growth, GDP at the current price and population. The data analysis technique used is the multiple linear sregression analysis method.The results showed that, simultaneously and partially the variables of fiscal decentralization and economic growth had a positive and significant effect on inter-regional inequality.Keywords: Fiscal Decentralization, Economic Growth, Regional Inequality